(untitled) (Conferencea, 2023)
This article explores the importance of tourism and its impact on the global economy. It highlights the benefits of tourism for both travelers and local communities and provides insights into popular tourist destinations worldwide. Additionally, it discusses the challenges faced by the tourism industry and the measures taken to ensure sustainable tourism practices.